Teacher commitment and student achivement in english reading comprehension in oyo town,Nigeria. (2024)
This study investigated the effect of teacher commitment to teaching on students’ academic achievement in English reading comprehension among senior secondary school 2 students in Oyo metropolis, Nigeria. The correlation research design was adopted. Two hundred and forty students and six teachers from six schools were purposively selected as participants for the study. The two instruments used were reading comprehension achievement test (r = 0.76) and teacher commitment to teaching questionnaire (r = 0.81). Three research questions were answered using frequency counts, percentage, and Pearson Product Moment Correlation. The findings revealed that teacher commitment to teaching is low, students achievement in reading comprehension is low, teacher commitment to teaching has no significant relationship with students achievement in English reading comprehension (r=.205). Based on these findings, it is recommended that teachers of English Language should be more committed to teaching for effectiveness.